Effects of dietary supplementation of saturated fatty acids and of n-6 or n-3 polyunsaturated fatty acids on plasma and red blood cell membrane phospholipids and deformability in weanling guinea pigs - Pöschl, Johannes; Paul, Karl; Leichsenring, Michael; Han, Shan R.; Pfisterer, Matthias; Bremer, Hans J.; Linderkamp, Otwin (Lipids, 1999)
The fatty acid composition of plasma cholesteryl esters, plasma phospholipids, red blood cell (RBC) membrane phosphatidylcholine (corresponding to the outer membrane leaflet), and phosphatidylethanolamine (corresponding to the inner membrane leaflet) was investigated in weanling guinea pigs fed with diets of cacao (saturated fatty acids), sunflower oil [n−6 polyunsaturated fatty acids (PUFA)] or fish oil (n−3 PUFA) for 20 wk. RBC deformation was measured by means of a cell-transit analyzer (filtration) and a cone-plate rheoscope. The contents of saturated fatty acids in plasma phospholipids and RBC membrane leaflets were similar in all three groups. Diets with sunflower oil resulted in a high content of linoleic acid in plasma cholesteryl esters and in the outer leaflet of RBC membranes. Fatty acids of fish oil were mainly incorporated in plasma phospholipids and in the inner leaflet of RBC membranes. The arachidonic acid content was high in all groups in the plasma phospholipids and in the inner leaflet. The n−6 and n−3 PUFA were mainly incorporated in the inner leaflet. In all groups the polyunsaturated/saturated fatty acid ratio and the total PUFA content were similar in the inner RBC membrane. The RBC filtration times and the RBC deformation indices were not affected by the dietary treatment.
Gesehen am 29.12.2020